VIRTUAL REALITY (VR) AND AUGMENTED REALITY (AR) AS TOOLS FOR IMPROVING GUEST ENGAGEMENT IN LUXURY HOTELS - Yuvasree G ,; Senthil Kumaran.v,; Arjun.K, (IJRDO - Journal of Applied Management Science, 2025)
Generally speaking, this dissertation delves into how virtual reality (VR) and augmented reality (AR) technologies can be implemented to improve guest engagement in luxury hotels. It seeks to address the challenge of pinpointing their real effectiveness and user experience in the hospitality sector. The research uses a mixed-methods approach, which analyzes guest feedback (qualitative data), engagement level metrics (quantitative data), and in-depth case studies from luxury hotels. These hotels have integrated VR and AR into their operations. The findings, in most cases, suggest that both technologies considerably boost guest interaction, satisfaction, and the emotional connection felt towards the hotel experience. VR, notably, was found to ease immersive pre-visit experiences. AR, on the other hand, enhanced real-time interaction with services and amenities, leading to engagement level increases of about 30%.These results, with some clarification, underscore the potential of VR and AR as transformative tools in the hospitality industry. This suggests that integrating these technologies not only elevates guest experiences but can provide a competitive advantage. This is especially important in an increasingly saturated market. The broader implications of this study reach beyond hospitality and into healthcare. It is here, where similar technologies *may* enhance patient engagement, education, and overall satisfaction. This advocates for application of these technologies in a variety of service-oriented fields. This research, [citeX], contributes valuable insights to understanding emerging technologies and their use in improving customer experience, [extractedKnowledgeX], also promoting further exploration into VR and AR’s transformational impacts across various industries.